1966
DOI: 10.1017/s0016672300009460
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on asymmetrical correlated responses to selection

Abstract: The pattern of changes of the genetic covariance between two characters on selection was examined in an effort to explain the asymmetry of correlated responses in two traits, or of the same trait in two environments, frequently observed in experimental results.The algebraic conclusions were further examined by model selection experiments using a computer. The computer was programmed to calculate the change in gene frequency from generation to generation and to calculate from it the expected changes in genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
1
1

Year Published

1969
1969
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 6 publications
4
157
1
1
Order By: Relevance
“…Indeed, correlated responses to selection not only depend on the genetic and phenotypic variance and covariance between the traits, but may also be influenced by population size, selection intensity, number of loci influencing the traits, allele frequencies, linkage disequilibrium, and pleiotropy (Falconer and Mackay 1996;Roff 1997). In fact, an asymmetrical correlated response to selection is a common evolutionary outcome for physiologically complex traits (Bohren et al 1966;Shiotsugu et al 1997;Czesak et al 2006 and references therein). For example, a recent selection experiment on home-cage activity in Hsd:ICR mice did not obtain a selection response (Zombeck et al 2011), whereas our selection experiment for wheel running (also using a base population of Hsd:ICR mice) produced a strong response in wheel running and a correlated response in home-cage activity (when housed without wheels: Rhodes et al 2005;Malisch et al 2009).…”
Section: Genetic Correlations and Correlated Responses To Selectionmentioning
confidence: 99%
“…Indeed, correlated responses to selection not only depend on the genetic and phenotypic variance and covariance between the traits, but may also be influenced by population size, selection intensity, number of loci influencing the traits, allele frequencies, linkage disequilibrium, and pleiotropy (Falconer and Mackay 1996;Roff 1997). In fact, an asymmetrical correlated response to selection is a common evolutionary outcome for physiologically complex traits (Bohren et al 1966;Shiotsugu et al 1997;Czesak et al 2006 and references therein). For example, a recent selection experiment on home-cage activity in Hsd:ICR mice did not obtain a selection response (Zombeck et al 2011), whereas our selection experiment for wheel running (also using a base population of Hsd:ICR mice) produced a strong response in wheel running and a correlated response in home-cage activity (when housed without wheels: Rhodes et al 2005;Malisch et al 2009).…”
Section: Genetic Correlations and Correlated Responses To Selectionmentioning
confidence: 99%
“…Genetic correlations are strongly influenced by gene frequencies and because selection changes the frequencies, genetic correlations can change after a few generations of selection (Bohren et al, 1969). Genetic correlations often have large sampling errors, especially when heritability estimates are low (e.g.…”
Section: General Considerationmentioning
confidence: 99%
“…deviations from predicted correlated responses have been frequently reported, especially under conditions of antagon istic selection (Clayton et al, 1957a;Bohren et al, 1966;Rutledge et al, 1973;Moll et al, 1975), use of a type II index would entail a risk of producing unsatis factory genetic changes in the population. By comparison, type III indices appeared to make greater use of direct responses and to be less dependent on correlations.…”
Section: Results Of Field Experimentsmentioning
confidence: 99%
“…Bohren et al (1966) indicated that such changes were to be expected as a result of antagon istic types of selection. Friars et al (1962) concluded that eight years of selection for four traits in poultry had generally reduced the positive genetic correlations among the traits.…”
Section: Application Of Index Selectionmentioning
confidence: 99%